Post-Zombie: Posthumanization of a Monster in Zombie Movies / Постзомби: постгуманизация монстра в современных фильмах о зомби - PAVLOV ALEXANDЕR V. / ПАВЛОВ А.В. (Наука телевидения, 2023)
Posthumanism—or, as the philosopher Francesca Ferrando calls it, the philosophy of our time—is in high demand both as a current of thought and as a theoretical tool for analyzing popular culture. The interdisciplinary field of zombie studies is also actively developing. The article proves that zombie studies are a legitimate field of humanities and social sciences. Scholars analyze zombies within the framework of sociology, ethics, neuroscience, international relations, literary studies, etc. As a theoretical tool, many of those studying zombies apply the philosophy of posthumanism. Until now, scholars have mostly been fascinated by the one zombie plot: the zombie apocalypse. However, there is another zombie-related narrative. Some call it a sentient zombie, humanizing the undead. In such a narrative, zombies are redefined, and to them the standard definition of a zombie no longer fits. A new image of the zombie can be revealed through the monster theory. The peculiar humanization of the zombie as a monster can be characterized as posthumanization. Since the classic image of the zombie in this case is redefined, we need to find a new term for the new monster. The author proposes to name the new sentient zombies post-zombies and suggests that their monstrosity should also be redefined, supporting these ideas through the analysis of Day of the Dead (1985), Warm Bodies (2013), and The Girl with All the Gifts (2016).